Enhancing Biology Cognitive Outcomes Through STEM Learning with Virtual Lab Gizmos - Jariah, Ainun; Arifin, Arifah Novia; Ainun, Nur Aisyah (Universitas Negeri Makassar, 2025)
Abstract. This quasi-experimental study evaluated the effect of STEM-based biology instruction supported by Virtual Lab Gizmos on students’ cognitive learning outcomes across academic ability levels. Sixty Grade-12 science students at a senior high school participated in a four-week intervention and were randomly assigned to experimental (STEM + Gizmos, n = 30) and control (contextual learning, n = 30) classes. Cognitive outcomes were measured with a validated 25-item test (Cronbach’s α = .89). Two-way ANCOVA controlling for pretest scores revealed significant main effects of learning approach (F = 62.67, p < .001) and academic ability (F = 179.95, p < .001), and a significant interaction (F = 4.19, p = .026). Post hoc LSD comparisons showed adjusted means of 92.00 (STEM-high), 86.33 (STEM-low), 82.17 (contextual-high), and 75.83 (contextual-low), indicating larger gains in the STEM + Gizmos groups. These results suggest that integrating STEM pedagogy with virtual laboratory simulations can substantially improve conceptual mastery and reduce achievement gaps. Future research should test longer interventions and diverse school contexts.Keywords: STEM learning; Virtual Lab Gizmos; cognitive outcomes; academic ability; biology education.